Improving The Knowledge Of Primary School Children On Fourth Grade Stundents About Vegetables And Fruits And Attraction Of Puzzle Media In SDN Mekarjaya I - Wiena Arynda; Rosmida M Marbun (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
In Indonesia, 93.5% of the population aged ≥10 years still consume less fruits and vegetables 5 servings per day for 7 days a week (RISKESDAS, 2013). The preliminary study conducted at SDN Mekarjaya I shows that the level of knowledge of school children about vegetables and fruits by 60% is still low and 93.3% of vegetable and fruit consumption is still lacking. In addition, SDN Mekarjaya I has never been used as a place of prior research. Therefore, it is necessary to conduct research on the knowledge of fruit vegetables in the fourth grade students of SDN Mekarjaya I. One of them is by doing counseling with the media of puzzle game. This research was conducted to know the increase of knowledge about vegetables and fruits before and after given counseling with puzzle game media in fourth grade students of SDN Mekarjaya I. This research was conducted by Pre-exsperiment method using "One group pretest and posttest" research design. Sampling by purposive sampling is 66 people. The statistical test used is paired sample t-test. Based on the results of the analysis shows that there is a significant difference of knowledge where p-value 0.000 or p <0,05 means there is a meaningful difference between before and after given counseling with puzzle game media.This puzzle game media can be developed by the teachers as a medium of learning in the classroom so that students are more motivated in following the learning process and make students do not feel bored